The Factors Affecting Cooperation and the Moderating Effect of Technological Turbulence - Siahaan, Arthur Tunggul; Suhartanto, Eko; Tercia, Christiana (International Research Journal of Business Studies, 2021)
This present study investigates the effect of technological turbulence on cooperation, the mediation role of non-economic satisfaction between focal constructs of relationship marketing (RM) and cooperation, and the effect of interpersonal commitment on interorganizational commitment. The findings show that high technological turbulence dampens the positive relationship of two focal constructs of RM, non-economic satisfaction mediates focal constructs of RM and cooperation, and interpersonal commitment influences interorganizational commitment. The study uses empirical data from business-to-business (B2B) ICT resellers in Indonesia to test the hypotheses developed. A structured questionnaire via an online platform is used as a research instrument with one hundred and one company participating.